Diagnosis and Treatment of Small Vessel Childhood Primary Angiitis of the Central Nervous System (sv-cPACNS): An International Survey - Keenan, Paul; Brunner, Jürgen; Quan, Angela S.; Smitka, Martin; Hahn, Gabriele; Pain, Clare E.; Häfner, Renate; Speth, Fabian; Gerstl, Lucia; Hedrich, Christian M. (Frontiers in Pediatrics, 2021)
Childhood primary angiitis of the Central Nervous System (cPACNS) is a rare autoimmune and inflammatory disease. It can result in significant neuronal damage, neurodevelopmental delay and potentially death. Childhood PACNS is divided into subcategories: angiography-positive p-cPACNS that affects medium and large vessels, and angiography-negative small vessel sv-cPACNS. Due to its rarity, variable clinical representation, and the lack of a diagnostic criteria and therapeutic plans, diagnosis and treatment of cPACNS is challenging and approaches vary. This survey collected information on diagnostic and therapeutic approaches to sv-PACNS. It was shared with international clinician networks, including the German Society for Paediatric Rheumatology, the Paediatric Rheumatology European Society, the “Network Paediatric Stroke,” and members of the American College of Rheumatology/CARRA Paediatric Rheumatology list server. This project has shown consensus in numerous diagnostic and therapeutic treatment approaches, highlighting key areas which will be utilized to develop statements in the use of expert consensus meetings to standardize diagnostic and therapeutic approaches in this rare inflammatory disease.